Lessons learned from a prolonged norovirus GII.P16-GII.4 Sydney 2012 variant outbreak in a long-term care facility in Portugal, 2017. (24th July 2019) - Sáez-López, Emma; Marques, Rodrigo; Rodrigues, Nuno; Oleastro, Mónica; Andrade, Helena; Mexía, Ricardo; de Sousa, Rita
Abstract: Objective: To investigate an outbreak of acute gastroenteritis caused by norovirus (NoV) in a long-term care facility (LTCF) in Portugal to describe and estimate its extent, and we implemented control measures. Design: Outbreak investigation. Methods: Probable cases were residents or staff members in the LTCF with at least 1 of the following symptoms: (1) diarrhea, (2) vomiting, (3) nausea, and/or (4) abdominal pain between October 31 and December 8, 2017. Confirmed cases were probable cases with positive NoV infection detected by real-time polymerase chain reaction (RT-PCR) and the same genotype in stool specimens. Results: The outbreak was caused by NoV GII.P16-GII.4 Sydney 2012 variant and affected 146 people. The highest illness rates were observed in residents (97 of 335, 29%) and nurses (16 of 83, 19%). All 11 resident wards were affected. Data on cases and their working or living areas suggest that movement between wards facilitated the transmission of NoV, likely from person to person. Conclusions: The delay in the identification of the causative agent, a lack of restrictions of resident and staff movement between wards, and ineffective initial deep-cleaning procedures resulted an outbreak that continued for >1 month. The outbreak ended only after implementation of strict control measures. Recommendations for controlling future NoV outbreaks in LTCFs include emphasizing the need to control resident's movements and to restrict visitors, timely and effective environmental cleaning and disinfection, leave of absence for ill staff, and encouraging effective hand hygiene.